ANALISIS KEPRIBADIAN INDIVIDU UNTUK BERSATU DI TENGAH PERBEDAAN BUDAYA - Nelsa Tonapa; Argita Argita; Suryani Suryani; Mint Husen Raya Aditama; Rinna Yuanita Kasenda (JUPE : Jurnal Pendidikan Mandala, 2022)
This study aims to determine the personality of individuals to unite amidst cultural differences. This research was conducted on the Manado State University campus in North Sulawesi. The research subjects selected in this study were 5 (five) students. This research is a qualitative type with a qualitative descriptive approach with observational and interview research types. Data analysis in this study begins with data collection, data reduction, data presentation, and finally draws conclusions. The results of this study indicate that the five subjects have given their opinions subjectively about culture, where culture is the customs and way of life of a group of people that have been passed down from generation to generation and each has its own uniqueness. Then they argue about their respective cultures, where there are various uniqueness and cannot be separated from various positive and negative sides. But in the midst of their unique culture, there are various individual personality differences, in terms of language, attitudes, facial expressions, tone of voice, which have their own characteristics, so that when they mingle, they feel happy, and they can get to know each other. add insight, respect each other and even understand each other, even though they are in the midst of cultural differences, they must remain united in accordance with the Indonesian nation's motto, namely Bhinneka Tunggal Ika, and with that difference is a strength for us to complement one another. This study aims to determine the personality of individuals to unite amidst cultural differences. This research was conducted on the Manado State University campus in North Sulawesi. The research subjects selected in this study were 5 (five) students. This research is a qualitative type with a qualitative descriptive approach with observational and interview research types. Data analysis in this study begins with data collection, data reduction, data presentation, and finally draws conclusions. The results of this study indicate that the five subjects have given their opinions subjectively about culture, where culture is the customs and way of life of a group of people that have been passed down from generation to generation and each has its own uniqueness. Then they argue about their respective cultures, where there are various uniqueness and cannot be separated from various positive and negative sides. But in the midst of their unique culture, there are various individual personality differences, in terms of language, attitudes, facial expressions, tone of voice, which have their own characteristics, so that when they mingle, they feel happy, and they can get to know each other. add insight, respect each other and even understand each other, even though they are in the midst of cultural differences, they must remain united in accordance with the Indonesian nation's motto, namely Bhinneka Tunggal Ika, and with that difference is a strength for us to complement one another.